A contrast in safety, pharmacokinetics and pharmacodynamics across age groups after a single 50 mg oral dose of the γ‐secretase inhibitor avagacestat. (14th December 2012) - Tong, Gary; Wang, Jun‐Sheng; Sverdlov, Oleksandr; Huang, Shu‐Pang; Slemmon, Randy; Croop, Robert; Castaneda, Lorna; Gu, Huidong; Wong, Oi; Li, Hewei; Berman, Robert M.; Smith, Christina; et al.
Abstract : WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT  Under homeostatic conditions, sequential cleavage of amyloid precursor protein by β‐site cleaving enzyme and γ‐secretase forms the common Aβ isoforms, Aβ1–38, Aβ1–40, and Aβ1–42 .  However, in the pathological Alzheimer's disease (AD) state, Aβ clearance is decreased nearly 30%. As such, γ‐secretase is a promising drug target for AD therapy, as a decrease in its enzymatic activity has the potential to reduce Aβ levels and modify disease.  In contrast, current treatments for AD provide only short term symptomatic relief. WHAT THIS STUDY ADDS  Unique among previous studies of γ‐secretase inhibitors (GSIs), such as semagacestat and begacestat, our results showed that avagacestat, an oral GSI in clinical development for the disease‐modifying treatment of AD, decreased Aβ1–40 plasma concentrations and was well‐tolerated in both young and elderly subjects, with adverse events being predominantly mild to moderate in severity. AIM To evaluate the single dose pharmacokinetics, pharmacodynamics, and preliminary tolerability of the γ‐secretase inhibitor BMS‐708163 (avagacestat) in young and elderly men and women. METHODS All subjects received double‐blinded administration of a single 50 mg dose of avagacestat in capsule form or matching placebo. Main evaluations included pharmacokinetics, safety, plasma amyloid‐β (Aβ)1–40 concentratios and exploration of Notch biomarkers. RESULTS Avagacestat 50 mg capsule was well tolerated and rapidly absorbed among young and elderly subjects, with a median t max between 1 and 2 h post dose and an average half‐life between 41 and 71 h. In general, subjects aged 75 years or more had higher AUC(0, ∞) values than those aged less than 75 years. An exploratory analysis of Aβ1–40 serum concentrations showed a pattern of decreasing concentrations over the first 4–6 h followed by a rise above baseline that was maintained until the end of the assessment period. Adverse events were generally mild, occurring more frequently in elderly subjects, with no observed difference between subjects receiving avagacestat and placebo. No dose limiting gastrointestinal effects of avagacestat were observed and exploratory biomarkers of Notch inhibition did not change significantly. CONCLUSIONS The favourable safety profile and pharmacokinetic effects of avagacestat in this study support its continued development, especially in the target population of elderly subjects with mild cognitive impairment or Alzheimer's disease.